Respons Perempuan Tani Terhadap Kebijakan Pemerintah Daerah dalam Mendorong Keberlanjutan Sektor Pertanian Lokal di Kecamatan Konda Kabupaten Konawe Selatan - Syaifudin Suhri Kasim; Ratna Supiyah; Aryuni Salpiana Jabar; Suharty Roslan; Megawati A. Tawulo; Asrani (Jurnal Neo Societal, 2025)
This research aims to analyze women farmers' responses to local government policies in encouraging the sustainability of the local agricultural sector in Konda District, South Konawe Regency. The research focus includes evaluating the level of participation of women farmers, the obstacles they face, and the impact of policies on economic and social sustainability in local farming communities. This research uses a qualitative approach with a case study method. Data was obtained through in-depth interviews, participatory observation, and analysis of regional policy documents related to the agricultural sector. Key informants consisted of women farmers, agricultural extension workers, local government officials and local community leaders. The research results show that women farmers in Konda District have an important role in supporting agricultural sustainability, especially through managing harvests, diversifying businesses, and strengthening social networks. . This research concludes that successful agricultural sustainability policies require stronger integration of gender perspectives, especially in providing equal access to resources and decision making.